Optical and photoconductivity spectra of novel Ag 2In 2SiS 6 and Ag 2In 2GeS 6 chalcogenide crystals - Chmiel, M.; Piasecki, M. M; Lakshminarayana, G.; Reshak, Ali Hussein, Prof. Dr.; Parasyuk, O. G. (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/